Charism and Saints of the Third Order of St. Francis in Chronicles of the Three Orders by Marco da Lisboa from 1610 - Puchalska-Dąbrowska, Bernadetta (Piśmiennictwo zakonne w dobie staropolskiej, 2013)
The aim of the article is to present the charism and role models of the Third Order of Saint Francis ofAssisi as described in the chronicles of the Order of the Friars Minor by Marco da Lisboa and translatedinto Polish in 1610. The ninth chapter of the second volume of the book contains interesting materialdivided into two parts. The first one is dedicated to the history of the Third Order, its rules and relatingpapal documents, while the second is a selection of the lives of saints belonging to the Order, such as St.Elizabeth of Hungary. The material under discussion allows the reader to reconstruct the structure of theThird Order in the 17th century and study the role models recommended to its members.